2009
DOI: 10.1002/cpp.644
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical integration of trauma memories and repressive coping predict post‐traumatic stress symptoms in undergraduate students

Abstract: What differentiates those who are able to adapt well to adverse life events (i.e., persons who are resilient) from those who are not (e.g., persons who develop post-traumatic stress symptoms)? Previous work suggests that enhanced autobiographical integration of trauma memories is associated with more severe post-traumatic stress symptoms. Extending this line of work, the present study looked at whether the integration of trauma memories, repressive coping and cognitive reactivity are related to post-traumatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 48 publications
2
19
0
3
Order By: Relevance
“…Consistent with the view that the accessibility of negative events is enhanced in many emotional disorders, robust positive correlations have been found between the CES for negative events and level of PTSD symptoms in relation to the event (Berntsen & Rubin, 2006; 2007; 2008; Boals, 2010; Robinaugh, & McNally, 2010; Rubin, Boals, & Berntsen, 2008; Rubin, Berntsen & Hutson, 2009; Schuettler & Boals, 2011; Smeets et al, 2010; Thomsen & Berntsen, 2009). This positive relationship has been found in a variety of populations suffering from different types of traumatic events.…”
Section: Effects Of Emotional Valence On the Long-term Accessibility supporting
confidence: 73%
“…Consistent with the view that the accessibility of negative events is enhanced in many emotional disorders, robust positive correlations have been found between the CES for negative events and level of PTSD symptoms in relation to the event (Berntsen & Rubin, 2006; 2007; 2008; Boals, 2010; Robinaugh, & McNally, 2010; Rubin, Boals, & Berntsen, 2008; Rubin, Berntsen & Hutson, 2009; Schuettler & Boals, 2011; Smeets et al, 2010; Thomsen & Berntsen, 2009). This positive relationship has been found in a variety of populations suffering from different types of traumatic events.…”
Section: Effects Of Emotional Valence On the Long-term Accessibility supporting
confidence: 73%
“…Berntsen and Rubin (2006) introduced the Centrality of Event Scale (CES) to examine the relation between the centrality of the traumatic memory and PTSD symptoms. An increasing number of studies in a variety of populations and with different types of traumatic events have shown that people reporting greater centrality of their most negative/traumatic event also score higher on measures of PTSD symptoms (e.g., Berntsen & Rubin, 2006;Boals, 2010;2012;Brown et al, 2010;Lancaster et al, 2011;Perri & Keefe, 2008;Robinough & McNally, 2011;Rubin, Berntsen & Hutson, 2009;Smeets, Giesbrecht, Raymaekers, Shaw, & Merckelbach, 2010;Thomsen & Berntsen, 2009). This positive relationship persists in regression analyses controlling for such factors as depression, thought control, anxiety, dissociation, Neuroticism, repressive coping, selfconsciousness and severity of the trauma (e.g., Berntsen & Rubin, 2007;Lancaster et al, 2011;Smeets et al, 2010).…”
Section: Characteristics Of the Memorymentioning
confidence: 99%
“…The CES contains such questions as “I feel that this event has become part of my identity.” “This event has become a reference point for the way I understand myself and the world.” “I feel that this event has become a central part of my life story.” “I often think about the effects this event will have on my future.” In contrast to the disintegration view, several studies have shown that the CES correlates positively (not negatively) with level PTSD symptoms. These studies include a variety of samples, including college students, combat veterans, women with a history of childhood sexual abuse, and community dwelling adults with a diagnosis of PTSD (Berntsen & Rubin, 2006, 2007, 2008; Brown, Antonius, Kramer, Root, & Hirst, 2010; Lancaster, Rodrigueza, & Westonb, 2011; Robinaugh & McNally, 2010, 2011; Smeets, Giesbrecht, Raymaekers, Shaw, Merckelbach, 2010; Schuettler, & Boals, 2011). …”
Section: Are Trauma Memories Incomplete Fragmented and Not Well Intmentioning
confidence: 99%